The Carian language - Adiego Lajara, Ignacio-Javier. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2007)
This handbook provides a complete and updated view of our current knowledge about Carian, one of the Indo-European languages spoken in ancient Anatolia. The decipherment of the Carian alphabet has only recently made it possible to analyze Carian inscriptions and to classify the Carian language linguistically. The book covers all major topics of research on Carian: the direct and indirect sources with an edition of the Carian inscriptions following a new classification system, the history of the decipherment, the Carian alphabet, and the phonological, morphological, lexical, and syntactic features of the language. It includes an annotated Carian glossary. The volume concludes with a special appendix on Carian coins and legends by Koray Konuk that will be of particular interest to specialists in ancient numismatics.